TAUHID SEBAGAI PARADIGMA EPISTEMIK DALAM PENDIDIKAN ISLAM: ANALISIS KRITIS TERHADAP PEMIKIRAN ISMAIL RAJI AL-FARUQI: (Analisis Kritis terhadap Pemikiran Ismail Raji Al-Faruqi) - Ahmad Sayyidiman Hamidalloh; Muhammad Arosyiddin (LPPI Universitas Al-Qolam Malang, 2026)
Abstract This study aims to analyze the concept of monotheism as an epistemic paradigm in Islamic education through a critical examination of the thought of Ismail Raji Al-Faruqi. The background of this research is based on the epistemological crisis in Islamic education, characterized by a dichotomy between religious and general knowledge and a weakening of value orientation in the educational process. This study uses a qualitative approach with library research and philosophical-critical analysis. The primary data sources come from Al-Faruqi's works relevant to the concept of monotheism and epistemology, supported by related secondary literature. The results indicate that monotheism in Al-Faruqi's thought functions as an epistemic paradigm that emphasizes the unity of truth, the unity of sources of knowledge, and the unity of reality. This paradigm has significant implications for Islamic education, particularly in building an integrative, holistic, and value-oriented educational system. However, the critical analysis reveals that Al-Faruqi's thought still has limitations, particularly in operationalizing the concept into concrete educational practices. Therefore, this study offers a conceptual reconstruction of tauhid as a more applicable epistemic paradigm through the development of an integrative curriculum, a values-based learning methodology, and the strengthening of the ethical dimension in education. This study confirms that tauhid has potential as an epistemological solution for Islamic education, but requires further development to be relevant to contemporary educational dynamics. Key words: Tawhid, epistemology, Islamic education, Ismail Raji Al-Faruqi, integration of knowledge